Regionalizing muscle activity causes changes to the magnitude and direction of the force from whole muscles—a modeling study - Rahemi, Hadi; Nigam, Nilima; Wakeling, James M. (Frontiers in Physiology, 2014)
Skeletal muscle can contain neuromuscular compartments that are spatially distinct regions that can receive relatively independent levels of activation. This study tested how the magnitude and direction of the force developed by a whole muscle would change when the muscle activity was regionalized within the muscle. A 3D finite element model of a muscle with its bounding aponeurosis was developed for the lateral gastrocnemius, and isometric contractions were simulated for a series of conditions with either a uniform activation pattern, or regionally distinct activation patterns: in all cases the mean activation from all fibres within the muscle reached 10%. The models showed emergent features of the fibre geometry that matched physiological characteristics: with fibres shortening, rotating to greater pennation, adopting curved trajectories in 3D and changes in the thickness and width of the muscle belly. Simulations were repeated for muscle with compliant, normal and stiff aponeurosis and the aponeurosis stiffness affected the changes to the fibre geometry and the resultant muscle force. Changing the regionalization of the activity resulted to changes in the magnitude, direction and centre of the force vector from the whole muscle. Regionalizing the muscle activity resulted in greater muscle force than the simulation with uniform activity across the muscle belly. The study shows how the force from a muscle depends on the complex interactions between the muscle fibres and connective tissues and the region of muscle that is active.